PENERAPAN MODEL KOOPERATIF TIPE PROBING-PROMPTING PADA MATERI INTEGRAL KELAS XI SMA - Fals, Iwan; Hartoyo, Agung; Nursangaji, Asep (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to find the effectiveness of the application of the probing-prompting type of cooperative model in learning integral materials of class XI SMA. The method used in this research is pre-experimental method with one-shot case study design. The aspects that be  used to determine the effectiveness of learning using probing-prompting type of cooperative model are teacher’s implementation in managing learning, student’s activities, student’s learning outcomes, and student’s responses. The used  data collection techniques are measurement, observation, and indirect communication techniques. The used data collection tools are the student’s learning outcomes test, which contain 4 essay questions, the observation sheet of teacher’s implementation in managing learning, the observation sheet of student’s activity and student’s responses questionnaire. The research data were analyzed descriptively and using one sample T-test. The result that obtained are teacher's implementation in managing learning is good, student’s activity is classified as active, student's learning completeness classically is not fulfilled ( = -1,6 < = 1,68), and very positive responses by the student. Because there is a criteria of the effectiveness that not fulfilled, so the learning using the application of the probing-prompting type of cooperative model in learning integral material at class XI SMA Negeri 4 Pontianak is not effective.Keywords: Application of learning, Probing-Prompting Type Of Cooperative Model, Integral Material